Ga(III) chelates of amphiphilic DOTA-based ligands : synthetic route and in vitro and in vivo studies - Fontes, André Filipe Gomes Soares (2011)
In this work we report a synthetic strategy of amphiphilic DOTA-based chelators bearing a variable size α-alkyl chain at one of the pendant acetate arms (from six to fourteen carbon atoms), compatible with their covalent coupling to amine-bearing biomolecules. The amphiphilic behavior of the micelles-forming Ga(III) chelates (critical micelle concentration), their stability in blood serum and their lipophilicity (logP) were investigated. Biodistribution studies with the 67Ga-labeled chelates were performed in Wistar rats showing a predominant liver uptake with almost no traces of the radiochelates in the body after 24 hours.